Postulat usunięcia terminu obyczajność z Kodeksu karnego - Piosik, Łukasz (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
In my article, I formulate and describe the demand to remove the term obyczajność (propriety) from the Penal Code. In the course of the analysis, I will attempt to prove that its presence in the Act is an example of cultivating a terminological tradition that dates back to the partitions period and was started for a reason that is currently outdated – the general language was insufficient to describe sexual crimes. I also show that due to the discrepancy between the general and legal language, the use of the term obyczajność may mislead a non-professional interpreter of a legal text. The text concludes with a more precise description of the titular demand, i.e. a proposal to change the title of Chapter 25 of the Penal Code.